PERLINDUNGAN WARGA NEGARA DARI DISKRIMINASI RAS DAN ETNIS - ., Triyanto (PKn Progresif, 2012)
All human beings are born free and equal in dignity and rights. Everyone is entitled to all the rights and freedoms set forth in this Declaration, without distinction of any kind, such as race, colour, sex, language, religion, political or other opinion, national or social origin, property, birth or other status. Indonesia gives guarantee for human rights protection by Law No.39 Year 1999 regarding Human Rights. For implementing this Law, Indonesia legislates Law No.40 Year 2008 regarding Elimination of Racial and Ethnic Discrimination.